Composite material, thin film, preparation method of thin film, light-emitting device and display device

By introducing a first material with crosslinking groups into the quantum dot material, the ligand is crosslinked with the crosslinking group, the problem of the quantum dot ligand being prone to breakage or shedding under power on is solved, and the electrical stability of the quantum dot material is improved.

CN119529842APending Publication Date: 2025-02-28TCL TECHNOLOGY GROUP CORPORATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311120033.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The ligands on the surface of quantum dots are prone to break bonds or fall off when powered on, affecting the stability of the quantum dots.

Method used

A composite material is used, which comprises a quantum dot and a first material having at least two crosslinking groups, and the ligand and the crosslinking groups are crosslinked to form a stable crosslinking system.

Benefits of technology

It improves the chemical stability of the ligand, prevents it from falling off or breaking the bond, and does not affect the carrier transmission performance of the quantum dots, effectively improving the electrical stability of the quantum dot materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529842A_ABST
    Figure CN119529842A_ABST
Patent Text Reader

Abstract

The invention discloses a composite material, a thin film, a preparation method of the thin film, a light-emitting device and a display device, the composite material comprises a quantum dot material and a first material, the quantum dot material comprises quantum dots and ligands connected to the surfaces of the quantum dots, and the first material has at least two crosslinking groups. The invention aims to improve the problem of poor long-term stability of the existing quantum dot material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of semiconductor technology, and in particular to a composite material, a thin film and a preparation method thereof, a light-emitting device and a display device. Background Art

[0002] Quantum dots (QDs) are nanocrystalline particles with a radius smaller than or close to the Bohr exciton radius. They have quantum confinement effects and can emit fluorescence when excited. Moreover, quantum dots have unique luminescence properties, such as wide excitation peak, narrow emission peak, and adjustable luminescence spectrum, which makes them have broad application prospects in the field of optoelectronic luminescence.

[0003] In order to improve the stability and dispersibility of quantum dots, ligands are usually attached to the surface of quantum dots. However, these ligands are prone to bond breaking when electricity is applied, causing changes in the chemical properties of the ligands or causing the ligands to fall off, which can easily affect the stability of quantum dots. Summary of the invention

[0004] In view of this, the present application provides a composite material, a film and a method for preparing the same, a light-emitting device and a display device.

[0005] The embodiment of the present application is implemented as follows:

[0006] In a first aspect, the present application provides a composite material including a quantum dot material and a first material, wherein the quantum dot material includes quantum dots and ligands connected to the surface of the quantum dots, and the first material has at least two cross-linking groups.

[0007] In a second aspect, the present application proposes a thin film, the material of which includes a composite material, the composite material includes a quantum dot material and a first material, the quantum dot material includes quantum dots and ligands connected to the surface of the quantum dots, the first material has at least two cross-linking groups; wherein at least part of the ligands are cross-linked with the cross-linking groups.

[0008] In a third aspect, the present application provides a method for preparing a thin film, comprising the following steps:

[0009] Providing composite materials;

[0010] depositing the composite material to obtain a thin film;

[0011] The composite material comprises a quantum dot material and a first material. The quantum dot material comprises quantum dots and ligands connected to the surfaces of the quantum dots. The first material has at least two cross-linkable groups.

[0012] In a fourth aspect, the present application proposes a light-emitting device, comprising a first electrode, a light-emitting layer and a second electrode, wherein the material of the light-emitting layer comprises the film described above, or comprises a film prepared by the preparation method described above.

[0013] In a fifth aspect, the present application proposes a display device, comprising the light-emitting device as described above.

[0014] The composite material proposed in the present application includes a quantum dot material and a first material. The ligands on the surface of the quantum dots can undergo a cross-linking reaction with the cross-linking groups in the first material. The ligands in the product after the reaction are cross-linked with the first material, thereby improving the chemical stability of the overall structure of the ligands, thereby effectively improving the electrical stability of the quantum dot material without significantly affecting the carrier transport properties of the quantum dots. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0016] Figure 1 is a structural schematic diagram of a light-emitting device proposed in an embodiment of the present application;

[0017] Figure 2 It is a schematic structural diagram of a material of a light-emitting layer of a light-emitting device proposed in an embodiment of the present application;

[0018] Reference numerals:

[0019] 100-light-emitting device; 10-anode; 20-light-emitting layer; 30-electron transport layer; 40-cathode; 50-hole transport layer; 60-hole injection layer; 1-quantum dot; 2-ligand; 3-first material. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0021] In this application, unless otherwise specified, directional words such as "upper" and "lower" used refer specifically to the directions of the drawings in the accompanying drawings. In addition, in the description of the specification of this application, the term "including" means "including but not limited to".

[0022] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0023] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0024] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0025] Explanation of terms

[0026] In the present application, "substituted or unsubstituted" means that the defined group may be substituted or unsubstituted. When the defined group is substituted, it is understood that the defined group may be substituted by one or more substituents. When substituted by multiple substituents, each substituent may be the same or different. In this article, each occurrence of a substituent is independently selected from one or more combinations of C1-C8 alkyl, C1-C8 alkoxy, amino, carboxyl, hydroxyl, mercapto, nitro, aryl with 6-12 ring carbon atoms, heterocyclic hydrocarbon with 5-12 ring atoms, and halogen groups.

[0027] In the present application, the "number of ring atoms" refers to the number of atoms among the atoms constituting the ring itself of a structural compound (for example, a monocyclic compound or a polycyclic compound) obtained by bonding atoms to form a ring. When the ring is substituted by a substituent, the atoms contained in the substituent are not included in the ring atoms. The same applies to the "number of ring atoms" described below unless otherwise specified. For example, the number of ring atoms of a benzene ring is 6, the number of ring atoms of a naphthalene ring is 10, and the number of ring atoms of a thienyl group is 5. The "number of ring carbon atoms" refers to the number of atoms among the carbon atoms constituting the ring itself. For example, the number of ring carbon atoms of a benzene ring is 6, and the number of ring carbon atoms of a pyridine ring is 5.

[0028] In the present application, "alkyl" may represent a straight chain alkyl or a branched chain alkyl. C1-10 alkyl refers to an alkyl group containing 1 to 10 carbon atoms, and each occurrence may be independently C1 alkyl, C2 alkyl, C3 alkyl, C4 alkyl, C5 alkyl, C6 alkyl or C10 alkyl. Non-limiting examples of alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, isobutyl, 2-ethylbutyl, 3,3-dimethylbutyl, n-pentyl, isopentyl, neopentyl, tert-pentyl, 1-methylpentyl, 3-methylpentyl, n-hexyl, etc.

[0029] In the present application, "alkylene" refers to a group derived from an alkane by removing two hydrogen atoms, that is, a group derived from an alkyl by removing another hydrogen atoms.

[0030] In the present application, "aryl" refers to a group derived from an aromatic ring compound containing a benzene ring by removing one hydrogen. The aromatic ring compound can be a single-ring aromatic ring, a condensed aromatic ring formed by a plurality of rings, or a non-condensed aromatic ring connected by a plurality of rings. For a polycyclic ring, at least one is an aromatic ring system. Suitable examples of aromatic ring compounds include, but are not limited to, benzene rings, naphthalene rings, biphenyl rings, anthracene rings, phenanthrene rings, naphthacene rings, fluorene rings, indene, etc. Correspondingly, the aryl groups corresponding to the above aromatic ring compounds are phenyl, naphthyl, biphenyl, anthracene, phenanthrene, naphthacene ring group, fluorene group, indenyl, etc.

[0031] In the present application, "heterocyclic hydrocarbon group" refers to a group derived from a heterocycle by removing a hydrogen atom. A heterocycle refers to an aromatic ring or a cyclic hydrocarbon group in which at least one carbon atom is replaced by a non-carbon atom. The non-carbon atom may be an N atom, an O atom, an S atom, a P atom, etc., and the number of non-carbon atoms may be 1 to 10. Suitable examples include, but are not limited to, thiophene, furan, pyrrole, imidazole, diazole, triazole, pyridine, bipyridine, pyrimidine, triazine, acridine, pyridazine, pyrazine, quinoline, isoquinoline, quinazoline, quinoxaline, phthalazine, pyridopyrimidine, pyridopyrazine, benzothiophene, benzofuran, indole, pyrroloimidazole, pyrrolopyrrole, thienopyrrole, thienothiophene, furanopyrrole, furanofuran, thienofuran, benzisoxazole, benzisothiazole, benzimidazole, o-naphthyridine, phenanthridine, primary dine, quinazolinone, dibenzothiophene, dibenzofuran, carbazole and derivatives thereof. A monoheterocyclic compound refers to a heterocyclic compound having only one ring, which may be a five-membered ring, a six-membered ring, etc.; a monoheterocyclic group refers to a group derived from a monoheterocyclic compound by removing one hydrogen; a condensed heterocyclic group refers to a group derived from a condensed heterocyclic compound by removing one hydrogen.

[0032] In the present application, an alkoxy group has a structural characteristic of the formula -OR; an amino group refers to -NR 1 R 2 ; hydroxyl refers to -OH; carboxyl refers to -COOH; nitro refers to -NO2; mercapto refers to -SH; halogen group refers to -F, -Br, -Cl or -I. Wherein, R refers to alkyl; Wherein, R 1 , R 2 Each is independently selected from H or alkyl.

[0033] In a first aspect, an embodiment of the present application proposes a composite material, which includes a quantum dot material and a first material 3, wherein the quantum dot material includes a quantum dot 1 and a ligand 2 connected to the surface of the quantum dot 1, and the first material has at least two cross-linking groups.

[0034] The composite material proposed in the present application includes a quantum dot material and a first material 3. The ligand 2 on the surface of the quantum dot 1 can undergo a cross-linking reaction with the cross-linking group in the first material 3. In the product after the reaction, the ligands 2 can be cross-linked with each other through the first material 3, thereby improving the chemical stability of the overall structure of the ligand 2, making it difficult to fall off or break the bond. Even if it falls off, the cross-linked ligand 2 will adhere to the surface of the quantum dot 1 and re-bond with the surface of the quantum dot 1 in the dynamic equilibrium of adsorption-detachment, thereby effectively improving the electrical stability of the quantum dot material without significantly affecting the carrier transport performance of the quantum dot 1. When the light-emitting layer 20 of the light-emitting device 100 is prepared using this material, it helps to improve the life of the device while avoiding affecting the luminous efficiency of the device.

[0035] In some specific embodiments, the first material 3 includes one or more compounds having a structure shown in formula (1);

[0036] Formula (1):

[0037]

[0038] in, is a cross-linking group;

[0039] L1 is selected from one or more combinations of ether group, substituted or unsubstituted C1-C20 alkylene group;

[0040] M1 is selected from O or CR3R4;

[0041] M2 is selected from O or CR5R6.

[0042] Specifically, when M1 is selected from O, the structural formula of the compound is as follows:

[0043]

[0044] When M1 is selected from CR3R4, the structural formula of the compound is as follows:

[0045]

[0046] When M2 is selected from O, the structural formula of the compound is as follows:

[0047]

[0048] When M2 is selected from CR5R6, the structural formula of the compound is as follows:

[0049]

[0050] Wherein, R1, R2, R3, R4, R5 and R6 are each independently selected from a combination of one or more of H, substituted or unsubstituted C1-C20 alkyl.

[0051] Wherein, each time the substituents of L1, R1, R2, R3, R4, R5 and R6 appear, they are independently selected from at least one of C1-C8 alkyl, C1-C8 alkoxy, amino, carboxyl, hydroxyl, mercapto, nitro, aryl having 6-12 ring carbon atoms, heterocyclic hydrocarbon having 5-12 ring atoms and halogen groups.

[0052] In some specific embodiments, the first material 3 includes one or more compounds having structures shown in formulas (2) to (10). Among them, the CAS of the compound having the structure shown in formula (2) is 591-93-5; the CAS of the compound having the structure shown in formula (3) is 3070-53-9; the CAS of the compound having the structure shown in formula (4) is 763-30-4; the CAS of the compound having the structure shown in formula (5) is 592-45-0; the CAS of the compound having the structure shown in formula (6) is 21964-49-8; the CAS of the compound having the structure shown in formula (7) is 2100-17-6; the CAS of the compound having the structure shown in formula (8) is 110-13-4; and the CAS of the compound having the structure shown in formula (9) is 924-41-4.

[0053]

[0054] Furthermore, in some embodiments, L1 is selected from unsubstituted C1-C20 alkylene groups; it has relatively small steric hindrance, and when the composite material is cross-linked to form a cross-linked body, it helps to shorten the distance between the quantum dots 1 and improve the conductivity.

[0055] In some embodiments, M1 is selected from CR3R4; which helps to improve the conductivity and cross-linkability of the material.

[0056] In some embodiments, M2 is selected from CR5R6; which helps to improve the conductivity and cross-linkability of the material.

[0057] In some embodiments, M1 is selected from CR3R4, and M2 is selected from CR5R6; accordingly, the structural formula of the compound is as follows: The compound has high conductivity and cross-linkability.

[0058]

[0059] In some embodiments, R1, R2, R3, R4, R5, and R6 are each independently selected from H or an unsubstituted C1-C20 chain hydrocarbon group; the structure of the first material 3 is more streamlined, the volume of the first material is smaller, the spacing between the quantum dots 1 can be reduced, and it helps to improve the conductivity of the material.

[0060] Furthermore, in some embodiments, L1 is selected from unsubstituted C1-C10 alkylene groups; the distance between the two double bonds is shortened, which helps to improve the conductivity of the material.

[0061] In some embodiments, at least one of R3 and R4 is selected from H; in some embodiments, at least one of R5 and R6 is selected from H.

[0062] Furthermore, in some embodiments, R3, R4, R5, and R6 are all selected from H, that is, the two double bonds are located at the ends of the main chain of the compound, which has smaller steric hindrance, is more conducive to cross-linking with the ligand, and has a simpler structure, which helps to improve the conductivity of the material.

[0063] In some specific embodiments, the first material 3 includes one or more compounds having structures shown in formulas (2) to (4). Relatively speaking, the compounds having structures shown in formulas (2) to (4) have better conductivity and cross-linkability, which helps to improve the stability and photoelectric performance of the composite material.

[0064]

[0065] In some embodiments, the ligand 2 can be a compound containing a first group and a second group at the same time, wherein the first group is selected from a group containing at least one carbon unit, and the carbon unit is CH, CH2, or CH3; the second group can be any binding group that can be connected to the surface of the quantum dot 1, and can include but is not limited to one or more of amino, carboxyl, sulfhydryl, phosphino, and phosphinyl. It should be noted that the CH in the carbon unit can undergo a cross-linking reaction with the double-bond cross-linking group in the first material 3; "binding group" refers to a group with the ability to bind, and there are many ways to bind. For example, when it is a carboxyl group, the ligand 2 raw material interacts with the inorganic semiconductor particles and binds, and its binding state is a carboxylic acid metal salt (the metal ion is a metal ion that is not coordinated on the surface of the quantum dot 1); when it is a phosphino, phosphinyl, sulfhydryl or amino group, a coordination bond is formed between the binding group of the ligand 2 raw material and the metal ion that is not coordinated on the surface of the quantum dot 1.

[0066] In some embodiments, the ligand 2 includes at least one of a substituted or unsubstituted C10-C24 chain organic carboxylic acid, a substituted or unsubstituted C10-C24 chain organic amine, a substituted or unsubstituted C1-C24 chain thiol, a substituted or unsubstituted C10-C24 chain organic phosphine, and a substituted or unsubstituted C10-C24 chain organic phosphine oxide. Each time the substituent of the ligand appears, it is independently selected from at least one of a C1-C8 alkyl group, a C1-C8 alkoxy group, an amino group, a carboxyl group, a hydroxyl group, a thiol group, a nitro group, an aromatic group having 6 to 12 ring carbon atoms, a heterocyclic hydrocarbon group having 5 to 12 ring atoms, and a halogen group. Specifically, the organic carboxylic acid includes decacarboxylic acid (CAS: 334-48-5), undecene, The organic amines include one or more of oleylamine (CAS: 112-90-3) and octadecylamine (CAS: 124-30-1); the organic (oxygen) phosphine includes one or more of trioctylphosphine (CAS: 4731-53-7) and trioctylphosphine oxide (CAS: 78-50-2); the thiol includes one or more of n-octyl mercaptan (CAS: 111-88-6), dodecanethiol (CAS: 112-55-0) and octadecyl mercaptan (CAS: 2885-00-9).

[0067] In some embodiments, the quantum dot 1 comprises at least one of a single structure quantum dot, a core-shell structure quantum dot and a perovskite semiconductor material; the material of the single structure quantum dot, the core material of the core-shell structure quantum dot and the shell material of the core-shell structure quantum dot are respectively selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound; the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, Z At least one of nSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSe At least one of Te, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe; the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, In At least one of PAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors.

[0068] As an example, the core-shell structured quantum dots may be selected from but not limited to at least one of CdZnSe / CdZnSe / ZnSe / CdZnS / ZnS, CdZnSe / CdZnSe / CdZnS / ZnS CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZnSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS and InP / ZnSe / ZnS.

[0069] It should be noted that, for the material of the aforementioned single structure quantum dot, or the material of the core of the core-shell structure quantum dot, or the material of the shell of the core-shell structure quantum dot, the chemical formula provided only indicates the elemental composition, but does not indicate the content of each element. For example, CdZnSe only indicates that it is composed of three elements, Cd, Zn and Se. If the content of each element is indicated, it corresponds to Cd x Zn 1-x Se,0 <x<1。

[0070] The inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of .

[0071] In some embodiments, in the composite material, the molar ratio of the first material 3 to the quantum dot material is (0.1-10):100; for example, it can be 0.1:100, 0.5:100, 1:100, 2:100, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100, 9:100, 10:100 and values ​​between any two of the above values. By controlling the molar ratio of the first material to the quantum dot material, the two can react to form a stable cross-linking system, thereby improving the chemical stability of the ligand 2 and ensuring the carrier transport performance of the quantum dots.

[0072] Furthermore, the present application also proposes a film, the material of which includes the composite material as described above. Under certain conditions, in the composite material, at least a portion of the ligands 2 on the surface of the quantum dot 1 undergoes a cross-linking reaction with at least a portion of the first material 3 to form a cross-linking system, thereby improving the chemical stability of the overall structure of the ligand 2, making it difficult to fall off or break bonds, and even if it falls off, the cross-linked ligands 2 will adhere to the surface of the quantum dot 1 and re-bond with the surface of the quantum dot 1 in a dynamic equilibrium of adsorption-detachment, thereby effectively improving the electrical stability of the quantum dot material without significantly affecting the carrier transport properties of the quantum dot 1. The film prepared using this material not only has better photoelectric properties, but also has higher stability.

[0073] In some embodiments, Figure 2 As shown, at least two of the ligands 2 connected to the quantum dots 1 are respectively cross-linked with the cross-linking groups of the same first material 3; and / or at least two of the ligands 2 connected to the quantum dots 1 are respectively cross-linked with the cross-linking groups of the same first material 3. The ligands and the first material form a cross-linking system in the film to improve the stability of the ligands.

[0074] Furthermore, the present application proposes a method for preparing a thin film. The preparation method comprises:

[0075] S100, providing a composite material, wherein the composite material includes the composite material described above;

[0076] S200, depositing the composite material to obtain a thin film.

[0077] During actual preparation, the composite material may be deposited on a substrate to form a thin film on the substrate. The substrate may be a glass substrate, a flexible substrate, or other film layers of the thin film to be prepared.

[0078] In specific implementation, step S200 may include:

[0079] S201, providing a solvent;

[0080] S202, mixing the composite material and the solvent to obtain a mixed solution;

[0081] S203, depositing the mixed solution, and then performing a thermal cross-linking reaction to obtain a thin film.

[0082] In some embodiments, the solvent includes one or more of n-hexane, n-pentane, n-heptane, benzene, toluene, chloroform, and dichloromethane.

[0083] In some embodiments, in the mixed solution, the concentration of the composite material is 10-40 mg / ml; for example, it can be 10 mg / ml, 15 mg / ml, 20 mg / ml, 25 mg / ml, 30 mg / ml, 35 mg / ml, 40 mg / ml and values ​​between any two of the above values.

[0084] In some embodiments, the temperature of the thermal cross-linking reaction is 100-140°C; for example, it can be 100°C, 110°C, 120°C, 130°C, 140°C and values ​​between any two of the above values. Controlling the temperature within this range can promote the cross-linking reaction between the double bonds in the first material 3 and the ligand 2.

[0085] In some embodiments, the thermal cross-linking reaction time is 10 to 60 minutes; for example, it can be 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes, and values ​​between any two of the above values.

[0086] In addition, the present application also proposes a light emitting device 100, see Figure 1 The light emitting device 100 includes a first electrode, a light emitting layer 20, and a second electrode. The first electrode may be one of the anode 10 and the cathode 40, and the second electrode may be the other of the anode 10 and the cathode 40.

[0087] For further information, see Figure 2In some embodiments, the light-emitting layer 20 includes the above-mentioned film, that is, the material of the light-emitting layer 20 includes the composite material as described above. Under certain conditions, in the composite material, at least a portion of the ligands 2 on the surface of the quantum dot 1 undergoes a cross-linking reaction with at least a portion of the first material 3 to form a cross-linking system, thereby improving the chemical stability of the overall structure of the ligand 2, making it difficult to fall off or break bonds, and even if it falls off, the cross-linked ligands 2 will adhere to the surface of the quantum dot 1 and re-bond with the surface of the quantum dot 1 in the dynamic equilibrium of adsorption-detachment, thereby effectively improving the electrical stability of the quantum dot material without significantly affecting the carrier transport properties of the quantum dot 1. When the light-emitting layer 20 of the light-emitting device 100 is prepared using this material, it helps to improve the life of the device while avoiding affecting the luminous efficiency of the device.

[0088] In some embodiments, the anode 10 can be an anode 10 for a light-emitting device 100 known in the art, for example, can be selected from but not limited to a doped metal oxide particle electrode, a composite electrode of a metal and a metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode, the material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide, the composite electrode of a metal and a metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba.

[0089] The cathode 40 can be a cathode 40 for the light-emitting device 100 known in the art, for example, can be selected from but not limited to a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode, the material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide, the composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, and the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba.

[0090] In some embodiments, the light-emitting device 100 further includes a hole functional layer disposed between the anode 10 and the light-emitting layer 20, and the hole functional layer includes one or two layers of a hole transport layer 50 and a hole injection layer 60. It should be noted that when the hole functional layer includes two layers of the hole transport layer 50 and the hole injection layer 60, the hole transport layer 50 is located between the hole injection layer 60 and the light-emitting layer 20. The material of the hole functional layer can be a material commonly used in the art that has hole injection or transport properties. For example, in some embodiments, the material of the hole transport layer 50 includes but is not limited to 4,4'-N,N'-dicarbazolyl-biphenyl (CBP), N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)- phenyl)-4,4'-diamine (TPD), N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro(spiro-TPD), N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine (DNTPD), tris(3-methylphenylphenylamino)-triphenylamine (m-MTDATA), poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butyl)phenyl)- phenyl) diphenylamine))] (TFB) and poly (4-butylphenyl-diphenylamine) (poly-TPD), polyaniline, polypyrrole, poly (p-) phenylene vinylene (PPV), poly [2-methoxy-5- (2-ethylhexyloxy) -1,4-phenylene vinylene] (MEH-PPV), poly [2-methoxy-5- (3',7'-dimethyloctyloxy) -1,4-phenylene vinylene] (MOMO-PPV), copper phthalocyanine, aromatic tertiary amines, multinuclear One or more of aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, poly(N-vinylcarbazole) (PVK) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N'-di(naphthalene-1-yl)-N,N'-diphenylbenzidine (NPB), and spiro NPB.The material of the hole injection layer 60 may include, but is not limited to, poly(ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine) (TFB), polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine (TPD), 4-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl (α-NPD), 4,4',4"-tris[phenyl(m-tolyl)amino]triphenylamine (m-MTDATA), 4,4',4 ”-tri(N-carbazolyl)-triphenylamine (TCTA), 1,1-bis[(di-4-tolylamino)phenylcyclohexane (TAPC), 4,4',4"-tri(diphenylamino)triphenylamine (TDATA) doped with tetrafluoro-tetracyano-quinodimethane (F4-TCNQ), p-doped phthalocyanine (e.g., F4-TCNQ-doped zinc phthalocyanine (ZnPc)), F4-TCNQ-doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), hexaazatriphenylene-capronitrile (HAT-CN) or one or more thereof.

[0091] In some embodiments, the light emitting device 100 further includes an electron transport layer 30 disposed between the light emitting layer 20 and the cathode 40. The material of the electron transport layer 30 may be a material known in the art for the light emitting device 100 and having electron transport properties, for example, may include but is not limited to one or more of metal oxides and doped metal oxides; the metal oxides include one or more of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3; the metal oxides in the doped metal oxides include multiple of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3, and the doping elements include one or more of Al, Mg, Li, In, Ga, Cd, Cs, and Cu.

[0092] It can be understood that the light emitting device 100 can be an upright device or an inverted device.

[0093] It is understandable that the light emitting device 100 may also be further provided with some functional layers conventionally used in the light emitting device 100 to help improve the performance of the light emitting device 100, such as an electron injection layer, an electron blocking layer, an interface modification layer, etc.

[0094] It can be understood that the material and thickness of each layer of the light emitting device 100 can be adjusted according to the actual requirements of the light emitting device 100 .

[0095] Based on the above embodiment of the light emitting device 100, a method for preparing the light emitting device 100 is further proposed, and the preparation method includes:

[0096] S10, providing a first electrode;

[0097] S20, providing a composite material, wherein the composite material includes the composite material described above;

[0098] S30, depositing the composite material on one side of the first electrode to form a light-emitting layer 20;

[0099] S40 , disposing a second electrode on a side of the light-emitting layer 20 away from the first electrode to obtain a light-emitting device 100 .

[0100] The first electrode is selected from one of the anode 10 and the cathode 40, and the second electrode is selected from the other of the anode 10 and the cathode 40. In actual preparation, according to the film layer design of the light-emitting device 100, it is determined whether to prepare the anode 10 or the cathode 40 first. For example, when the light-emitting device 100 is designed with the anode 10 at the bottom layer and the cathode 40 at the top layer, the anode 10 is prepared first, and the first electrode is the anode 10.

[0101] In specific implementation, step S30 may include:

[0102] S31, providing a solvent;

[0103] S32, mixing the composite material and the solvent to obtain a mixed solution;

[0104] S33 , depositing the mixed solution on one side of the first electrode, and then performing a thermal cross-linking reaction to obtain a light-emitting layer 20 .

[0105] In some embodiments, the solvent includes one or more of n-hexane, n-pentane, n-heptane, benzene, toluene, chloroform, and dichloromethane.

[0106] In some embodiments, in the mixed solution, the concentration of the composite material is 10-40 mg / ml; for example, it can be 10 mg / ml, 15 mg / ml, 20 mg / ml, 25 mg / ml, 30 mg / ml, 35 mg / ml, 40 mg / ml and values ​​between any two of the above values.

[0107] In some embodiments, the temperature of the thermal cross-linking reaction is 100-140°C; for example, it can be 100°C, 110°C, 120°C, 130°C, 140°C and values ​​between any two of the above values. Controlling the temperature within this range can promote the cross-linking reaction between the double bonds in the first material 3 and the ligand 2.

[0108] In some embodiments, the thermal cross-linking reaction time is 10 to 60 minutes; for example, it can be 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes, and values ​​between any two of the above values.

[0109] In some embodiments, the light-emitting device 100 further includes a plurality of functional film layers disposed between the first electrode and the second electrode, such as a hole transport layer 50, a hole injection layer 60, an electron transport layer 30, etc. In actual preparation, the preparation of a plurality of functional film layers is further included between step S10 and step S40. Specifically, the plurality of film layers can be prepared in sequence according to a preset order of the plurality of film layers to obtain the light-emitting device 100. In some embodiments, the plurality of film layers include a light-emitting layer 20, a hole transport layer 50, a hole injection layer 60, and an electron transport layer 30. The preset order of multiple film layers can be adjusted according to the device type. For example, the order of film layers of the upright device is anode 10, hole injection layer 60, hole transport layer 50, light emitting layer 20, electron transport layer 30, cathode 40 stacked from bottom to top; accordingly, in actual preparation, after completing step S10 and preparing anode 10, hole injection layer 60, hole transport layer 50, light emitting layer 20, electron transport layer 30 can be prepared on anode 10 in sequence, and finally step S40 is performed on electron transport layer 30 to prepare cathode 40. The order of film layers of the inverted device is opposite to that of the upright device. Accordingly, in actual preparation, cathode 40, electron transport layer 30, light emitting layer 20, hole transport layer 50, hole injection layer 60, anode 10 are prepared in sequence.

[0110] In some embodiments, each film layer can be realized by conventional techniques in the art, such as chemical methods or physical methods. Among them, chemical methods include chemical vapor deposition, continuous ion layer adsorption and reaction, anodization, electrolytic deposition, and coprecipitation. Physical methods include physical coating and solution methods, among which physical coating includes: thermal evaporation coating, electron beam evaporation coating, magnetron sputtering, multi-arc ion coating, physical vapor deposition, atomic layer deposition, pulsed laser deposition, etc.; solution methods can be spin coating, printing, inkjet printing, doctor blade coating, printing, dip-coating, immersion, spraying, roller coating, casting, slit coating, and strip coating, etc.

[0111] In addition, the present application also proposes a display device, which includes the light-emitting device 100 as described above, or includes the light-emitting device 100 manufactured by the manufacturing method as described above.

[0112] The display device can be any electronic product with a display function, including but not limited to smart phones, portable phones, tablet computers, personal digital assistants (PDA), portable multimedia players (Portable Multimedia Player), televisions, game consoles, watch-type electronic devices, head-mounted displays, personal computer displays, laptop computers, car navigation systems, car dashboards, digital cameras, portable cameras, external advertising boards, electro-optical panels, medical devices, detection devices, refrigerators, washing machines, etc.

[0113] The technical scheme and technical effects of the present application are described in detail below through specific embodiments and comparative examples. The following embodiments are only some embodiments of the present application and do not specifically limit the present application.

[0114] Material Example 1

[0115] (1) 128 mg of CdO powder was dissolved in a mixed solution of 2 ml of oleylamine (OA) and 20 ml of octadecene (ODE), and a uniform cadmium precursor solution was produced under continuous stirring at 240°C. 2.5 mmol of Se was dissolved in 5 ml of TOP, and the mixture was mixed under continuous stirring at 120°C to prepare a selenium precursor solution. The cadmium precursor solution and the selenium precursor solution were mixed, and heated at 240°C to obtain quantum dots CdSe with oleylamine attached to the surface.

[0116] (2) The quantum dots with oleylamine attached to the surface and the first material are mixed in a molar ratio of 100:10 and dispersed in n-hexane to obtain a composite material solution with a composite material concentration of 20 mg / ml. The first material is a compound having a structure shown in formula (2).

[0117] Material Example 2

[0118] The scheme of this embodiment is basically the same as that of embodiment 1, except that in step (2) of this embodiment, the first material is a compound having a structure shown in formula (3).

[0119] Material Example 3

[0120] The scheme of this embodiment is basically the same as that of embodiment 1, except that in step (2) of this embodiment, the first material is a compound having a structure shown in formula (4).

[0121] Material Example 4

[0122] The scheme of this embodiment is basically the same as that of embodiment 1, except that in step (2) of this embodiment, the first material is a compound having a structure shown in formula (5).

[0123] Material Example 5

[0124] The scheme of this embodiment is basically the same as that of embodiment 1, except that in step (2) of this embodiment, the first material is a compound having a structure shown in formula (6).

[0125] Material Example 6

[0126] The scheme of this embodiment is basically the same as that of embodiment 1, except that in step (2) of this embodiment, the first material is a compound having a structure shown in formula (7).

[0127] Material Example 7

[0128] The scheme of this embodiment is basically the same as that of embodiment 1, except that in step (2) of this embodiment, the first material is a compound having a structure shown in formula (8).

[0129] Material Example 8

[0130] The scheme of this embodiment is basically the same as that of embodiment 1, except that in step (2) of this embodiment, the first material is a compound having a structure shown in formula (9).

[0131] Material Example 9

[0132] The scheme of this embodiment is basically the same as that of embodiment 1, except that in step (2) of this embodiment, the molar ratio of the quantum dots having oleylamine connected to the surface and the first material is changed to 100:5.

[0133] Material Example 10

[0134] The scheme of this embodiment is basically the same as that of embodiment 1, except that in step (2) of this embodiment, the molar ratio of the quantum dots having oleylamine connected to the surface and the first material is changed to 100:0.1.

[0135] Material Example 11

[0136] The scheme of this embodiment is basically the same as that of embodiment 1, except that in step (2) of this embodiment, the molar ratio of the quantum dots having oleylamine connected to the surface and the first material is changed to 100:20.

[0137] Material Example 12

[0138] The scheme of this embodiment is basically the same as that of embodiment 1, except that in step (1) of this embodiment, the ligand is changed from oleylamine to oleic acid.

[0139] Comparative Example 1

[0140] The comparative example is basically the same as Example 1, except that in this comparative example, the composite material solution is changed to a quantum dot solution. Specifically, step (2) is changed to: dispersing quantum dots with oleylamine attached to the surface in n-hexane to obtain a quantum dot solution with a concentration of 20 mg / ml.

[0141] Comparative Example 2

[0142] This comparative example is basically the same as Example 12, with the only difference being that, in this comparative example, the composite material solution is changed to a quantum dot solution. Specifically, step (2) is changed to: dispersing quantum dots with oleic acid attached to the surface in n-hexane to obtain a quantum dot solution with a concentration of 20 mg / ml.

[0143] Device Example 1

[0144] The preparation method of the QLED device in this embodiment is as follows:

[0145] (1) PEDOT:PSS was spin-coated on the ITO anode at a rotation speed of 5000 rpm for 30 seconds, followed by heating at 150°C for 15 minutes to obtain a hole injection layer.

[0146] (2) Spin coating the hole injection layer with TFB chlorobenzene solution at a rotation speed of 3000 rpm for 30 seconds, followed by UV treatment for 10 minutes and then heating at 200° C. for 10 minutes to obtain a hole transport layer.

[0147] (3) The composite material solution prepared in Example 1 was spin-coated on the surface of the hole transport layer at a rotation speed of 2000 rpm for 30 seconds, and then heated at 120° C. for 30 minutes to obtain a light-emitting layer.

[0148] (4) Spin-coat a ZnO ethanol solution (concentration of 30 mg / mL) on the light-emitting layer at a spin-coating speed of 3000 rpm for 30 s, and then heat at 80° C. for 30 min to obtain an electron transport layer.

[0149] (5) Ag is deposited on the surface of the electron transport layer by thermal evaporation to form a cathode; wherein the vacuum degree is 3×10 -4 Pa, speed is The time is 1000s, the thickness is 100nm, and the packaging is performed to obtain a top-emitting upright QLED device.

[0150] Device Examples 2 to 12

[0151] The scheme of device embodiment n is basically the same as embodiment 1, with the only difference being that in device embodiment n, in step (3), the composite material solution used is changed to the composite material solution prepared in material embodiment n, and n is 2 to 12.

[0152] Device Comparative Examples 1 to 2

[0153] The device comparative example m is basically the same as Example 1, except that in the device comparative example n, in step (3), the composite material solution used is changed to the quantum dot solution prepared in the material comparative example m, and m is 1 to 2.

[0154] Experimental Example 1

[0155] Take the composite material solution prepared in the above material examples and comparative examples, take a glass substrate, spin-coat the composite material solution on the substrate at a speed of 2000 rpm for 30 seconds, and then heat at 120° C. for 30 minutes to obtain a thin film; take the thin film for performance stability test.

[0156] The test method is: place the film in an electric field environment (voltage is 5V, electric field strength is 1.6×10 -7 V / m), and the fluorescence quantum yield (PLQY) was measured at 0 day and 14 day, respectively, and the PLQY stability was calculated as follows.

[0157] PLQY stability = 14-day PLQY / 0-day PLQY × 100%;

[0158] Among them, the fluorescence quantum yield (PLQY) detection method is: put the film into the built-in integrating sphere of the Edinburgh spectrometer to compare the incident photons with the photons emitted by the quantum dot solution.

[0159] Table 1

[0160] PLQY stability (%) Material Example 1 96% Material Example 2 95% Material Example 3 95% Material Example 4 92% Material Example 5 88% Material Example 6 85% Material Example 7 83% Material Example 8 87% Material Example 9 94% Material Example 10 92% Material Example 11 88% Material Example 12 95% Material Comparative Example 1 11% Material Comparative Example 2 14%

[0161] From the table above we can see that:

[0162] The material examples 1 to 11 have much higher stability than the material comparative example 1, and the material example 12 has much higher stability than the material comparative example 2, indicating that the addition of the first material to the quantum dot material can improve the electrical stability of the quantum dot material;

[0163] In addition, compared with other embodiments, material embodiments 1 to 3 have higher stability, indicating that the compound having any structure shown in formula (2) to (4) is more conducive to improving the stability of quantum dot materials.

[0164] Experimental Example 2

[0165] Take the devices prepared in the above device embodiments and device comparative examples and test their maximum brightness L max , lifespan T95 and T95 1000nits. The results are recorded in Table 2.

[0166] Life test refers to the time taken for the device brightness to decay to a certain percentage of the maximum brightness under 2mA constant current drive. The time taken for the brightness to decay to 95% of the maximum brightness is defined as T95, and this life is the measured life. In order to shorten the life test cycle, the device life test is usually carried out at high brightness by accelerating device aging, and the life at low brightness is obtained by fitting the decay fitting formula. For example, the life at 1000nits is recorded as T95 1000nits, and the calculation formula is:

[0167]

[0168] Among them, T95 L The lifespan under low brightness, generally 1000nits, T95 H is the lifespan under high brightness, that is, the measured lifespan, L H is the maximum brightness that the device is accelerated to, L L Generally it is 1000nits, A is the acceleration factor, which is 1.7.

[0169] Table 2

[0170]

[0171]

[0172] Refer to Table 2, we can see that:

[0173] Device Examples 1 to 11 have higher L max , T95 and T95@1000nits, the material example 12 has a higher L than the device comparative example 2 max , T95 and T95@1000nits, indicating that the use of composite materials to prepare the light-emitting layer can not only extend the service life of the device, but also help to improve its light-emitting effect;

[0174] In addition, compared with other embodiments, device embodiments 1 to 3 have higher stability, indicating that when the first material is a compound having a structure shown in any one of formulas (2) to (4), its corresponding composite material is more conducive to improving the stability of the device.

[0175] The composite materials, thin films and preparation methods thereof, light-emitting devices and display devices provided in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the methods and core ideas of the present application. At the same time, for technical personnel in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A composite material, characterized in that: The invention comprises a quantum dot material and a first material. The quantum dot material comprises quantum dots and ligands connected to the surfaces of the quantum dots. The first material has at least two cross-linking groups.

2. The composite material according to claim 1, characterized in that The first material includes one or more compounds having a structure shown in formula (1); Formula (1): in, is a cross-linking group; L1 is selected from one or more combinations of substituted or unsubstituted C1-C20 alkylene groups; M1 is selected from O or CR3R4; M2 is selected from O or CR5R6; R1, R2, R3, R4, R5, and R6 are each independently selected from a combination of one or more of H, substituted or unsubstituted C1-C20 alkyl; Each time the substituents of L1, R1, R2, R3, R4, R5 and R6 appear, they are independently selected from at least one of C1-C8 alkyl, C1-C8 alkoxy, amino, carboxyl, hydroxyl, mercapto, nitro, aryl having 6-12 ring carbon atoms, heterocyclic hydrocarbon having 5-12 ring atoms and halogen groups.

3. The composite material according to claim 1, characterized in that The ligand includes at least one of substituted or unsubstituted C10-C24 chain organic carboxylic acids, substituted or unsubstituted C10-C24 chain organic amines, substituted or unsubstituted C1-C24 chain thiols, substituted or unsubstituted C10-C24 chain organic phosphines, and substituted or unsubstituted C10-C24 chain organic phosphine oxides. Each time the substituent of the ligand appears, it is independently selected from at least one of C1-C8 alkyl, C1-C8 alkoxy, amino, carboxyl, hydroxyl, mercapto, nitro, aromatic groups with 6-12 ring carbon atoms, heterocyclic hydrocarbon groups with 5-12 ring atoms, and halogen groups.

4. The composite material according to claim 2, characterized in that L1 is selected from unsubstituted C1-C20 alkylene; and / or, M1 is selected from CR3R4; and / or, M2 is selected from CR5R6; and / or, R1, R2, R3, R4, R5 and R6 are each independently selected from H or an unsubstituted C1-C20 chain hydrocarbon group.

5. The composite material according to claim 4, characterized in that L1 is selected from unsubstituted C1-C10 alkylene; and / or, At least one of R3 and R4 is selected from H; and / or, At least one of R5 and R6 is selected from H.

6. The composite material according to claim 5, characterized in that The first material includes one or more compounds having structures shown in formulas (2) to (9): 。 7. The composite material according to claim 3, characterized in that The substituted or unsubstituted C10-C24 chain organic carboxylic acid includes one or more of decadecanoic acid, undecenoic acid, tetradecanoic acid, oleic acid and stearic acid; the substituted or unsubstituted C10-C24 chain organic amine includes one or more of oleylamine and octadecylamine; the substituted or unsubstituted C1-C24 chain thiol includes one or more of n-octyl mercaptan, dodecanethiol and octadecyl mercaptan; the substituted or unsubstituted C10-C24 chain organic phosphine includes trioctylphosphine; the substituted or unsubstituted C10-C24 chain organic phosphine oxide includes trioctylphosphine oxide; and / or, The quantum dots include at least one of single structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials; the material of the single structure quantum dots, the core material of the core-shell structure quantum dots and the shell material of the core-shell structure quantum dots are respectively selected from at least one of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds; the II-VI group compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, H At least one of CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbS at least one of eTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe; the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNA s, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of .

8. The composite material according to claim 1, characterized in that In the composite material, the molar ratio of the quantum dot material to the first material is 100:(0.1-10).

9. A film, characterized in that: The material of the film includes a composite material, the composite material includes a quantum dot material and a first material, the quantum dot material includes quantum dots and ligands connected to the surface of the quantum dots, and the first material has at least two cross-linking groups; wherein at least part of the ligands are cross-linked with the cross-linking groups.

10. The film according to claim 9, characterized in that The first material includes one or more compounds having a structure shown in formula (1); Formula (1): in, is a cross-linking group; L1 is selected from one or more combinations of substituted or unsubstituted C1-C20 alkylene groups; M1 is selected from O or CR3R4; M2 is selected from O or CR5R6; R1, R2, R3, R4, R5, and R6 are each independently selected from a combination of one or more of H, substituted or unsubstituted C1-C20 alkyl; Each time the substituents of L1, R1, R2, R3, R4, R5 and R6 appear, they are independently selected from at least one of C1-C8 alkyl, C1-C8 alkoxy, amino, carboxyl, hydroxyl, mercapto, nitro, aryl having 6-12 ring carbon atoms, heterocyclic hydrocarbon having 5-12 ring atoms and halogen groups.

11. The film according to claim 9, characterized in that In the composite material, the molar ratio of the quantum dot material to the first material is 100:(0.1-10); and / or, The raw material of the ligand includes at least one of substituted or unsubstituted C10-C24 chain organic carboxylic acid, substituted or unsubstituted C10-C24 chain organic amine, substituted or unsubstituted C1-C24 chain thiol, substituted or unsubstituted C10-C24 chain organic phosphine, substituted or unsubstituted C10-C24 chain organic phosphine oxide, and the substituent of the ligand is independently selected from at least one of C1-C8 alkyl, C1-C8 alkoxy, amino, carboxyl, hydroxyl, mercapto, nitro, aromatic group with 6-12 ring carbon atoms, heterocyclic hydrocarbon group with 5-12 ring atoms and halogen group each time it appears; and / or, The first material includes one or more compounds having structures shown in formulas (2) to (9):

12. A method for preparing a thin film, characterized in that: The following steps are involved: Providing composite materials; depositing the composite material to obtain a thin film; The composite material comprises a quantum dot material and a first material, wherein the quantum dot material comprises quantum dots and ligands connected to the surface of the quantum dots, and the first material has at least two cross-linkable groups.

13. The preparation method according to claim 12, characterized in that: The first material includes one or more compounds having a structure shown in formula (1); Formula (1): in, is a cross-linking group; L1 is selected from one or more combinations of substituted or unsubstituted C1-C20 alkylene groups; M1 is selected from O or CR3R4; M2 is selected from O or CR5R6; R1, R2, R3, R4, R5, and R6 are each independently selected from a combination of one or more of H, substituted or unsubstituted C1-C20 alkyl; Each time the substituents of L1, R1, R2, R3, R4, R5 and R6 appear, they are independently selected from at least one of C1-C8 alkyl, C1-C8 alkoxy, amino, carboxyl, hydroxyl, mercapto, nitro, aryl having 6-12 ring carbon atoms, heterocyclic hydrocarbon having 5-12 ring atoms and halogen groups; In the film, at least a portion of the ligands and at least a portion of the first material are cross-linked with each other.

14. The preparation method according to claim 12, characterized in that: In the composite material, the molar ratio of the quantum dot material to the first material is 100:(0.1-10); and / or, The raw material of the ligand includes at least one of substituted or unsubstituted C10-C24 chain organic carboxylic acid, substituted or unsubstituted C10-C24 chain organic amine, substituted or unsubstituted C1-C24 chain thiol, substituted or unsubstituted C10-C24 chain organic phosphine, substituted or unsubstituted C10-C24 chain organic phosphine oxide, and the substituent of the ligand is independently selected from at least one of C1-C8 alkyl, C1-C8 alkoxy, amino, carboxyl, hydroxyl, mercapto, nitro, aromatic group with 6-12 ring carbon atoms, heterocyclic hydrocarbon group with 5-12 ring atoms and halogen group each time it appears; and / or, The first material includes one or more compounds having structures shown in formulas (2) to (9):

15. The preparation method according to claim 12, characterized in that: The step of depositing the composite material to obtain a thin film comprises: providing a solvent; mixing the composite material and the solvent to obtain a mixed solution; The mixed solution is deposited and then subjected to a thermal cross-linking reaction to obtain a thin film.

16. The preparation method according to claim 15, characterized in that: The solvent includes one or more of n-hexane, n-pentane, n-heptane, benzene, toluene, chloroform, and dichloromethane; and / or, In the mixed solution, the concentration of the composite material is 10-40 mg / ml; and / or, The temperature of the thermal crosslinking reaction is 100-140° C.; and / or, The time of the thermal crosslinking reaction is 10 to 60 minutes.

17. A light emitting device, characterized in that: The invention comprises a first electrode, a light-emitting layer and a second electrode, wherein the light-emitting layer comprises the thin film according to any one of claims 9 to 11, or comprises a thin film prepared by the preparation method according to any one of claims 12 to 16.

18. The light emitting device according to claim 17, characterized in that: In the light-emitting layer, at least a portion of the ligands and at least a portion of the first material are cross-linked with each other; and / or, The first electrode and the second electrode are each independently selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode. The material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide. The composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS. The material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba.

19. A display device, characterized in that: Comprising the light emitting device according to claim 17 or 18.